1978
DOI: 10.2307/3897668
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Anti-Coyote Electric Fencing

Abstract: Highlight: An electric fence with alternating ground and charged wires was tested for anti-coyote properties. Under the conditions tested, the fence was coyote proof. The fence may evolve as an effective, nonlethal method of preventing coyote depredation of domestic livestock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Electric fencing has been used to contain and protect livestock and agriculture since the 1960s and was initially constructed with smooth steel wire (Cadwallader 1992). Electric fencing is inexpensive, costing approximately $2,000/km (Miller et al 1992) and has been successfully used in the United States to reduce white-tailed deer damage (VerCauteren et al 2006a) and to protect livestock from coyotes (Gates et al 1978). However, steel-wire electric fencing is relatively permanent and cannot be moved or reused easily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric fencing has been used to contain and protect livestock and agriculture since the 1960s and was initially constructed with smooth steel wire (Cadwallader 1992). Electric fencing is inexpensive, costing approximately $2,000/km (Miller et al 1992) and has been successfully used in the United States to reduce white-tailed deer damage (VerCauteren et al 2006a) and to protect livestock from coyotes (Gates et al 1978). However, steel-wire electric fencing is relatively permanent and cannot be moved or reused easily.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, electric fencing has been proven effective for other free-ranging wildlife. For example, electric fencing has effectively excluded or inhibited movements of coyotes (Canis latrans; Gates et al 1978 Karhu and Anderson 2006).…”
mentioning
confidence: 99%
“…Dorrance and Bourne (1980) reported that coyotes still penetrated a 7-strand electric fence they used, even though the bottom wire (15-cm above ground level) was electrified. Gates et al (1978) found that 111-cm-high fencing was not effective at preventing coyotes from entering pastures. Only coyote-proof fencing (150-168-cm high with 12 strands) reduced coyote access to pastures (Gates et al 1978;Linhart et al 1982).…”
Section: Study Sitesmentioning
confidence: 92%
“…Gates et al (1978) found that 111-cm-high fencing was not effective at preventing coyotes from entering pastures. Only coyote-proof fencing (150-168-cm high with 12 strands) reduced coyote access to pastures (Gates et al 1978;Linhart et al 1982). VerCauteren et al (2006) reported that common livestock-fencing designs (e.g.…”
Section: Study Sitesmentioning
confidence: 92%
“…The fences were tested with and without electrification under controlled conditions to enable their effectiveness and pig behaviour to be clearly observed. A similar experimental appproach was used to test fences for coyote control (Gates et al 1978;Thompson 1979), and rat control (Shumake et al 1979).…”
Section: Introductionmentioning
confidence: 99%